INSTANT SHOPPING – MILLENNIAL USER IN BATAM CITY DURING COVID-19 PANDEMIC SERVICES - Edy Yulianto Putra (Faculty of Economic and Business, University of Pasundan, 2021)
Online shopping has been really familiar for both public and smarthone users. Recent phenomenon has showed us a much-helpful simple way in providing customers’ needs and consumption during Covid-19 pandemic. The limited space caused by the condition has made consumers shift towards instant online shopping. The customers’ changing behaviour forces business sector to adjust and fulfil customer’s need and desires. This research is implemented by using judgemental sampling method, which includes millennial generation as users on instant shopping. The amount of population is unknown, while the sample calculation is 1:10 of each questionnaire statement. Partial least square is also used in this research as analysis method, by also using SmartPLS 3.0. The result gave an analysis and found a slight change of customer’s behaviour, especially in using Instagram account as an instant shopping alternative which supports recent situation. This could also be next suggestion for further development after Covid-19 pandemic.